Characterisation and management of dermatologic adverse events to agents targeting the PD-1 receptor. (June 2016) - Belum, V.R.; Benhuri, B.; Postow, M.A.; Hellmann, M.D.; Lesokhin, A.M.; Segal, N.H.; Motzer, R.J.; Wu, S.; Busam, K.J.; Wolchok, J.D.; Lacouture, M.E.
Abstract: Background: Dermatologic adverse events (AEs) are some of the most frequently observed toxicities of immune-checkpoint inhibitor therapy, but they have received little attention. The drugs, pembrolizumab and nivolumab are recently approved inhibitors of the programmed death (PD)-1 receptor that have overlapping AE profiles however, the incidence, relative risk (RR), and clinico-morphological pattern of the associated dermatologic AEs are not known. Methods: We conducted a systematic review of the literature, and performed a meta-analysis of dermatologic AEs observed with the use of pembrolizumab and nivolumab in cancer patients. An electronic search was conducted using the PubMed, and Web of Science, and on the American Society of Clinical Oncology and European Society for Medical Oncology meeting abstracts' libraries for potentially relevant oncology trials, that employed the drugs at Food and Drug Administration-approved doses and reported dermatologic AEs. The incidence, RR and 95% confidence intervals were calculated using either random- or fixed-effects models based on the heterogeneity of included studies. The clinical presentation, histology of affected skin areas, and management strategies (based on institutional experience), are also presented. Results: Rash, pruritus and vitiligo were found to be the most frequently reported dermatologic AEs. The calculated incidence of all-grade rash with pembrolizumab and nivolumab was 16.7% (RR = 2.6) and 14.3% (RR = 2.5), respectively. Other significant all-grade AEs included pruritus (pembrolizumab: incidence, 20.2% [RR = 49.9]; nivolumab: incidence, 13.2% [RR = 34.5]) and vitiligo (pembrolizumab: incidence, 8.3% [RR = 17.5]; nivolumab: 7.5% [RR = 14.6]). Interestingly, all the vitiligo events were reported in trials investigating melanoma. The RR for developing dermatologic AEs in general, was 2.95 with pembrolizumab, and 2.3 with nivolumab. Conclusion: We found that pembrolizumab and nivolumab are both associated with dermatologic AEs, primarily low-grade rash, pruritus, and vitiligo, which are reminiscent of those seen with ipilimumab. Knowledge of these findings is critical for optimal care, maintaining dose intensity, and health-related quality of life in cancer patients receiving PD-1 inhibitors. Highlights: This is the first meta-analysis to ascertain the incidence and risk of developing dermatologic adverse events (AEs) during treatment with the recently approved programmed death (PD)-1 inhibitors, pembrolizumab and nivolumab. Skin rash, pruritus, and vitiligo are the most commonly reported AEs, although they appear to be primarily low-grade and manageable. Among the PD-1 inhibitor–induced skin rashes, the maculopapular morphology is most frequent, often portraying a lichenoid tissue reaction/interface dermatitis on histology.